T Peak–T End Interval Alteration as Parameter of Successful Fibrinolysis in Patients with ST Segment Elevation Acute Myocardial Infarction - Windhi Dwijanarko; Erika Maharani; Dyah Wulan Anggrahini (ACI (Acta Cardiologia Indonesiana), 2017)
Background: In STEMI patients, the duration of action potential dispersion occurs between normal and ischemic tissue due to the lengthening of the refractory period, causing transmural dispersion of repolarization, which could be detected with Tp-Te interval prolongation on the electrocardiogram (ECG). Benefits of fibrinolytic therapy in patients with STEMI has been demonstrated, with reduced mortality significantly and improve coronary patency in order to increase myocardial perfusion. The goal of this study was to determine Tp-Te interval alteration in STEMI patients before and after the fibrinolytic therapy between successful fibrinolysis compared to failed fibrinolysis. Method: Cross-sectional study was conducted to collect ECG from medical records at Dr. Sardjito General Hospital in January–September 2016. STEMI patients with onset less than 12hours whom reperfused with fibrinolytic therapy were registered. Tp-Te interval was measured before, soon after (0 minute), and 30 minutes after fibrinolysis with successful and failed results. The unpaired t-test analysis was used to compare Tp-Te interval alteration after fibrinolysis. Then, ΔTp-Te cut-off value was determined to find sensitivity and specificity based on ROC. Result: Among 84 patients enrolled in this study, 46 patients with successful fibrinolysis and 38patients with failed fibrinolysis. Both of groups had Tp-Te interval prolongation before fibrinolysis, with mean value of 120.30 ± 13.02 ms in successful fibrinolysis group and 118.57 ± 15.24 ms in failed fibrinolysis group. In successful fibrinolysis group, Tp-Te interval reduced significantly with ΔTp-Te value of 17.55 ± 13.35 ms on 0 minute and 20.85 ± 15.62 ms on 30 minutes after fibrinolysis, while in failed fibrinolysis group there was not a decrease of Tp-Te interval with ΔTp-Te value of -0.77 ± 11.00 ms on 0 minute (p <0.001) and -1.53 ± 14.35 ms on 30 minutes after fibrinolysis (p <0.001). Cut-off value ΔTp-Te 20 ms had sensitivity 52.2% and specificity 94.7% based on ROC, with strong discriminator value of AUC (0.888). Conclusion: There was a greater reduction of Tp-Te interval in STEMI patients with successful fibrinolysis compared to failed fibrinolysis, so it may be used as a alternative parameter of successful fibrinolysisKeywords: STEMI; Tp-Te interval; fibrinolysis